Balance Performance During Perturbed Standing Is Not Associated With Muscle Strength and Power in Young Adults. Issue 5 (3rd September 2017) - Zemková, Erika; Jeleň, Michal; Kováčiková, Zuzana; Miklovič, Peter; Svoboda, Zdeněk; Janura, Miroslav
ABSTRACT: The authors investigate the ways in which varied postural responses to translating platform perturbations are associated with the variables of strength and power. Twenty-four physically active and 27 sedentary young adults were exposed to a set of postural perturbations at varied velocities (10 and 20 cm/s) and the respective accelerations (6.4 and 6.9 m/s 2 ), constant distance (6 cm), and 4 directions of platform motion (forward, backward, left-lateral, and right-lateral). They also performed maximum voluntary isometric contraction (MVC) and chair rising/chair jumping tests. The analysis of variance revealed significant interaction effect for peak center of pressure displacement, direction by velocity: F 3, 129 = 24.43, p = .002; and direction by acceleration: F 3, 129 = 34.18, p = .001. There were no significant correlations between peak center of pressure displacements and peak force and peak rate of force development measured during MVC in either standing ( r = .27–57) or sitting positions ( r = .12–51) and peak power during chair jumping ( r = .47–.59) in all participants. As such, only a small proportion of variance was explained (9–39%, 3–23%, and 23–41%, respectively). In conclusion, interaction effects indicate that the composition of stimuli strongly influences compensatory responses and this effect is more pronounced in sedentary than in physically active young adults. Nevertheless, the dynamic balance is not associated with muscle strength and power in either group.